Preparation, characterization and catalytic performance of rod-like Ni–Nb–O catalysts for the oxidative dehydrogenation of ethane at low temperature. Issue 13 (7th June 2019) - Kong, Lian; Li, Dong; Zhao, Zhen; Li, Jianmei; Zhao, Linlin; Fan, Xiaoqiang; Xiao, Xia; Xie, Zean
Abstract : Improved catalytic performance as well as stability over Ni–Nb–O catalysts by hydrothermal method. Abstract : Ni–Nb mixed oxides are a system of high-efficiency catalysts for the oxidative dehydrogenation of ethane to ethylene (ODHE) in the presence of O2 . In this work, a series of Ni–Nb–O catalysts with various Nb contents (0, 5, 10, 15, 20 and 30 at%) were prepared by a PEG-4000-assisted one-pot hydrothermal method and evaluated as catalysts for the ODHE at low temperature. The Ni–Nb–O catalysts present excellent catalytic activity and selectivity to ethylene with promising stability. The prepared catalysts were characterized by means of XRD, N2 adsorption–desorption, SEM, TEM, H2 -TPR, O2 -TPR and Raman spectroscopy. XRD and TEM results explicitly manifest that a Ni–Nb solid solution formed, stemming from the Nb doped into the NiO crystal lattice. The reducibility is improved and unselective oxygen species are eliminated, as evidenced by H2 -TPR and O2 -TPD results. A comparison of the catalytic properties between bulk NiO and Ni–Nb–O catalysts was made, and Ni–Nb–O catalysts present improved efficiency for the production of ethylene. The significantly enhanced selectivities of ethylene are obtained over Ni–Nb–O catalysts, in which ethane conversion is also improved slightly. The elevated catalytic performance could be associated with smaller NiO crystal size, regular structure, reduction of electrophilic O − species and formation of a Ni–Nb solution. The catalytic performance of the catalysts changes with the variation of Nb content, which indicates that the incorporation of niobium into the NiO phase plays a critical role in the adjustment of catalytic performance. The Ni–Nb–O catalysts containing an optimum niobium content of 15 and 20 at% display higher catalytic performance with 47.5% and 47% ethylene yield at 400 °C, respectively. The Ni85 Nb15 composite is stable and an ethylene selectivity of ∼84% could be sustained after 56 h on-stream operation at 350 °C.